2022
DOI: 10.3233/jpd-223454
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals a Two-Gene Signature Links to Motor Progression and Alterations of Immune Cells in Parkinson’s Disease

Abstract: Background: The motor impairment in Parkinson’s disease (PD) can be managed but effective treatments for stopping or slowing the disease process are lacking. The advent of transcriptomics studies in PD shed light on the development of promising measures to predict disease progression and discover novel therapeutic strategies. Objective: To reveal the potential role of transcripts in the motor impairment progression of patients with PD via transcriptome analysis. Methods: We separately analyzed the differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Li et al [122], observed 17 A-t o-I editing sites in NCOR1, BST1, and KANSL1 genes with potential risk associations for PD in a study of 380 PD and 178 healthy controls samples from PPMI. Additionally, alterations in ADAR editing at 57 sites correlated with the progression of cognitive symptoms in PD patients [122].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Li et al [122], observed 17 A-t o-I editing sites in NCOR1, BST1, and KANSL1 genes with potential risk associations for PD in a study of 380 PD and 178 healthy controls samples from PPMI. Additionally, alterations in ADAR editing at 57 sites correlated with the progression of cognitive symptoms in PD patients [122].…”
Section: Discussionmentioning
confidence: 99%
“…ADAR2 and 3 expression was also highest in either prodromal or PD samples depending on whether sexes are combined. Other studies have observed decreased editing frequency [121] and significant differences in ADAR expression [122] in PPMI PD blood; however, these studies did not compare PD males to PD females or PD to prodromal in their analyses and included samples regardless of age; whereas, we chose samples from individuals 65 years or older.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations